Agricultural, domestic and handicraft folk uses of plants in the Tyrrhenian sector of Basilicata (Italy) - Guarrera Paolo; Salerno Giovanni; Caneva Giulia (BMC, 2005)
Abstract Background Research was carried out into agricultural and domestic-handicraft uses in folk traditions in the Tyrrhenian sector of the Basilicata region (southern Italy), as it is typically representative of ethnobotanical applications in the Mediterranean area. From the point of view of furnishing a botanical support for the study of local "material culture" data was collected through field interviews of 49 informants, most of whom were farmers. Results The taxa cited are 60, belonging to 32 botanical families, of which 18 are employed for agricultural uses and 51 for domestic-handicraft folk uses. Data show a diffuse use of plants for many purposes, both in agricultural (present uses 14%; past uses 1%) and for domestic-handicraft use (present uses 40%; past uses 45%); most of the latter are now in decline. Conclusion 60 data look uncommon or typical of the places studied. Some domestic-handicraft folk uses are typical of southern Italy (e.g. the use of Ampelodesmos mauritanicus for making ties, ropes, torches, baskets or that of Acer neapolitanum for several uses). Other uses (e.g. that of Inula viscosa and Calamintha nepeta for peculiar brooms, and of Origanum heracleoticum for dyeing wool red) are previously unpublished.